Marathon or sprint? Do elite-level athletes live longer than average? - Mayhew, L.; Algar, R. (International Longevity Centre, 2023)
We know that playing sport has many advantages. Aside from its health benefits, it can have a positive influence on younger participants, encouraging leadership qualities; it can lead to greater career success, and offer a route out of poverty if played to a high enough level. What we don`t know is whether it adds years to your life, as well as life to your years. The ILC previously posed this question in The longevity of sporting legends (2021), which investigated the longevity of leading male sports stars across seven sports, ranging from football to horseracing. The results showed that sports such as tennis and golf tended to provide the biggest boost to longevity, in part because they could be played into old age. The Commonwealth Games are an important global force. Since the 2006 Games in Melbourne, the event`s estimated global audience has remained steady at approximately 1.5 billion people - or around six out of ten people across the Commonwealth nations. Last summer England celebrated the success of the Commonwealth Games held in Birmingham. 1.5 million tickets were sold - a record for the Games- while the BBC TV audience was a record 28.6 million, making this one of the most successful Games ever. Like all established sporting events, the Games keep meticulous records of competing athletes, and especially medal winners. In this report, we use this information on medal winners, and much more, to investigate whether medallists live longer lives than the general public. We cover as many sports as possible with the information available, across a range of categories: track and field, indoor and contact sports, aquatics and cycling. But not all sports have been represented in every Games and so there are gaps. In addition, we disregard team sports such as basketball, cricket and rugby sevens, whose inclusion in the Games has been sporadic and for which the historical record is much harder to investigate. For men, we find that track, indoor and aquatics boost longevity the most — with aquatics connected to an increase (compared to the general male population) of 29%, track events 25%, and indoor sports 24%. This translates into between 4.5 and 5.3 extra years of life — an advantage that remains relatively constant over time despite general improvements in life expectancy. Marathon or sprint? Do elite-level athletes live longer than average? We didn`t have enough information to assess the life span of female athletes by sport, so we were forced to aggregate the results from all event categories. This is because women started competing in the Games later than men, and originally in fewer categories (although they now compete for more medals than men). We found that across all sports categories, their longevity is boosted 22%, equating to 3.9 extra years of life. Further findings show that the longevity of long distance runners is marginally higher than for those who run other distances; that wrestlers live longer than boxers; but that there`s no difference within field events. Neither do we find any evidence that gold medal winners live longer than silver or bronze medallists — so excelling in your chosen sport is enough! Cycling was the only exception. This is a relatively dangerous sport at a competitive level, involving a higher incidence of death and injury than for non-competitors. Longevity was only 90% compared with the general male population, although improved safety is changing this. You don`t have to be in your physical prime to win either. The 2022 Games produced the event`s oldest-ever gold medallist: George Miller of Scotland (born 1946) triumphed in the Para-Lawn Bowls Mixed Pairs aged 75, alongside his visually impaired countrywoman Melanie Innes (born 1964). The overwhelming message is that sport adds years to your life, as long as it`s not a dangerous one. While generally you can`t take part in sports at the highest level throughout your life, the benefits evidently stay with you long after your hang up your spikes or your swimming goggles!